Comparison of COVID-19 Laboratory Diagnosis by Commercial Kits: Effectivity of RT-PCR to the RT-LAMP - ARTIK, YAKUP; Coşgun, Alp B.; Cesur, Nevra P.; Hızel, Nedret; Uyar, Yavuz; Sur, Haydar; AYAN, ALP (Wiley, 2022)
Coronavirus disease 2019 or COVID-19 caused by novel coronavirus/severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or 2019-nCoV) is an ongoing pandemic that has emerging global effects and requires rapid and reliable diagnostic testing. Quantitative reverse transcription-polymerase chain reaction (q-RT-PCR) is the gold standard method for SARS-CoV-2 detections. On the other hand, new approaches remedy the diagnosis difficulties gradually. Reverse transcription loop-mediated isothermal amplification (RT-LAMP) as one of these novel approaches may also contribute to faster and cheaper field-based testing. The present study was designed to evaluate this rapid screening diagnostic test that can give results in 30-45 min and to compare the effectiveness of LAMP to the q-RT-PCR. The 30 randomly chosen patient samples were generated by nasopharyngeal swabs with a portion of the SARS-CoV-2 nucleic sequence. The sample of quantification cycle (Cq) values was tested using RT-LAMP as well as by conventional q-RT-PCR. The patient samples were tested with four different kits (SENSObiz COVID-19 [SARS-CoV-2] LAMP Assay, the QIAseq DIRECT SARS-CoV-2 kit, Biospeedy SARS-CoV-2 Variant Plus kit, and CoVirion-CV19-2 SARS-CoV-2 OneStep RT-PCR kit) and two different PCR devices (GDS Rotor-Gene Q Thermocycler and Inovia Technologies GenX series). Based on 30 patient samples, the positive/negative ratio (P/N) was 30/0 as Biospeedy and Covirion (positivity 100%), 28/2 as Qiagen kit (positivity 93.3%) for the samples studied on the Inovia device while the same samples on the Rotor-Gene device were 30/0 as Biospeedy and Covirion (positivity 100%), 29/1 as Qiagen kit at the first day (96.7%). On the fifth day, the samples were studied in the Inovia device and the respective results were obtained: 27/3 as Biospeedy (positivity 90%), 16/14 as Qiagen (positivity 53.3%), 28/2 as Covirion kit (positivity 93.3%). When these samples were studied in the Rotor-Gene device, it was 29/1 in Biospeedy and Covirion (positivity 96.7%), 19/11 in the Qiagen kit (positivity 63.3%). When these samples were compared with the LAMP method it was found to be 19/11 (positivity 63.3%) on the first day and 18/12 (positivity 60%) on the fifth day. SARS-CoV-2 test studies will contribute to a proactive approach to the development of rapid diagnosis systems. The LAMP approach presents promising results to monitor exposed individuals and also improves screening efforts in potential ports of entry.
Keywords: Coronavirus; Covid‐19; LAMP‐PCR; q‐RT‐PCR; SARS‐CoV‐2